2022
DOI: 10.3389/fpsyt.2022.986797
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between social support and parenting sense of competence in puerperal women: Multiple mediators of resilience and postpartum depression

Abstract: BackgroundMaternal role competence is an important marker of achievement in the role of the mother, but parenting sense of competence (PSOC) among puerperal women is not high. Psychosocial factors, particularly social support, postnatal depression and resilience, have been identified as significant predictors of maternal role competence. However, information is limited regarding the mechanisms through which these psychosocial factors affect maternal role competence.ObjectiveTo evaluate the multiple mediators o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Psychological factors such as anxiety and depression have been studied about CD, 26 but the roles of other factors such as social support have been poorly investigated. The high correlations of social support factors with psychological distress symptoms in patients with CD are consistent with a previous study about other illnesses 27 and indicate that the three factors of social support are likely a concept that reflects another dimension of psychological states. Social support is defined as behavioural or emotional support provided by family members, other people or other groups.…”
Section: Discussionsupporting
confidence: 88%
“…Psychological factors such as anxiety and depression have been studied about CD, 26 but the roles of other factors such as social support have been poorly investigated. The high correlations of social support factors with psychological distress symptoms in patients with CD are consistent with a previous study about other illnesses 27 and indicate that the three factors of social support are likely a concept that reflects another dimension of psychological states. Social support is defined as behavioural or emotional support provided by family members, other people or other groups.…”
Section: Discussionsupporting
confidence: 88%
“…These forms of assistance are key facilitators for mothers adjusting to their new role [ 16 ]. When Chinese mothers received emotional support and practical help with infant care from family, friends, or professionals, it helped them adapt to stress and emotional challenges during the postpartum period, reducing the incidence of postpartum depression and coping difficulties [ 7 , 8 ]. Furthermore, in Chinese mothers, receiving higher levels of support regarding parenting information and postpartum care needs, including bathing, feeding, and dressing their infants, was associated with fewer postpartum coping difficulties [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…A review of research on social support among first-time mothers in China found that a lack of social support made mothers’ role transition difficult, reduced satisfaction with their maternal role, and decreased their sense of parenting fulfillment, satisfaction, and happiness [ 7 ]. Difficulties in postpartum coping, stemming from inadequate infant care skills, were found to correlate negatively with postpartum social support [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations